Adherence to pan‐genotypic glecaprevir/pibrentasvir and efficacy in HCV‐infected patients: A pooled analysis of clinical trials. (18th October 2019) - Brown, Ashley; Welzel, Tania M.; Conway, Brian; Negro, Francesco; Bräu, Norbert; Grebely, Jason; Puoti, Massimo; Aghemo, Alessio; Kleine, Henning; Pugatch, David; Mensa, Federico J.; Chen, Yaozhu J.; et al.
Abstract: Background & Aims: Adequate adherence to hepatitis C virus (HCV) treatment is believed to be a key component of treatment success because non‐adherence can potentially result in treatment failure and the emergence of resistant viral variants. This analysis assessed factors associated with non‐adherence to glecaprevir/pibrentasvir (G/P) therapy and the impact of non‐adherence on sustained virological response at post‐treatment week 12 (SVR12) rates in HCV genotype (GT) 1‐6‐infected patients. Methods: Adherence was calculated by pill counts at study visits during treatment, and defined as having a lowest treatment adherence of ≥80% and ≤120% at each study visit. Exploratory logistic regression modelling assessed predictors of non‐adherence to G/P therapy. SVR12 rates by treatment adherence were assessed in the intent‐to‐treat (ITT) population and modified ITT (mITT) population, which excludes non‐virological failures. Results: Overall, 97% (2024/2091) of patients were adherent to G/P therapy at all consecutive study visits. Alcohol use was the only baseline characteristic independently associated with non‐adherence to G/P therapy (OR: 2.38; 95% CI: 1.13‐5.01; P = .022). In the mITT population, overall SVR12 rates were high both in patients who were adherent to G/P therapy and those who were not (99% [1983/2008] and 95% [58/61] respectively; P = .047). Corresponding SVR12 rates in the ITT population were 98% (1983/2024) and 87% (58/67) respectively. Conclusions: Most patients adhered to G/P therapy. SVR12 rates were high both in patients who were adherent to G/P treatment and those who were not. Patient education on treatment adherence should remain an important part of HCV treatment. Clinical trials registration: NCT02604017, NCT02640482, NCT02640157, NCT02636595, NCT02642432, NCT02651194, NCT02243293, NCT02446717.